On the Biochemistry and Biophysics of Living Cell Formation - Robertson, D. S. (Cell biochemistry and biophysics, 2023)
A description is given of a sequence of events which would have led to the appearance of the organic compounds and living cells present on Earth, one of which is human cells. The evolutionary events involved are proposed as having taken place in phosphate ion-dominated aqueous pools formed in regions associated with volcanoes. The mechanism involved the unique molecular structure variations and chemical properties of polyphosphoric acid and compounds of this acid producing urea as the first organic compound formed on Earth and derivatives of urea giving rise to DNA and RNA. The occurrence of the process in present times is considered possible.